Enhancing Student Preparedness and School Safety Through Disaster Simulation: A Comprehensive Analysis and Policy Implications - Muhammad Navis Mirza (International Journal of Educational Technology Research, 2023)
Disaster simulation in schools has become an increasingly important aspect of efforts to improve student preparedness and safety in various countries. This article explains the importance of disaster simulation as an effective tool for preparing students to face various natural disasters and emergency incidents in the school environment. This simulation method has been proven to increase students' understanding of the actions to be taken during emergency situations, as well as providing opportunities to identify potential risks and weaknesses in school emergency plans. The methodology used in this article includes literature analysis, case studies, and a review of disaster simulation programs that have been implemented in various schools. The research results show that disaster simulations are effective in increasing student preparedness and reducing the potential negative impacts of disasters in the school environment. The discussion includes the benefits, challenges, and policy implications of using disaster simulations in schools. The conclusion of this article is that disaster simulation is an important investment in student safety and preparedness, and needs to continue to be improved in educational contexts.